Differentiation of West Nile and St. Louis Encephalitis Virus Infections by Use of Noninfectious Virus-Like Particles with Reduced Cross-Reactivity - Roberson, Jill A. (American Society for Microbiology, 2007)
Differential diagnosis of St. Louis encephalitis virus (SLEV) and West Nile virus (WNV) infections can be complicated due to the high degree of cross-reactivity observed in most serodiagnostic assays. In an effort to provide a more specific diagnostic test, we developed virus-like particle (VLP) antigens with reduced cross-reactivity for both SLEV and WNV by identifying and mutating envelope protein amino acids within the cross-reactive epitopes of VLP expression plasmids. To determine the serodiagnostic discriminatory ability of the antigens with reduced cross-reactivity, a panel of 134 human serum samples collected predominately from North American patients with SLEV or WNV infections was used to evaluate the performance of these novel antigens in imunoglobulin M antibody-capture enzyme-linked immunosorbent assays. Positive/negative ratios and the resulting diagnostic classifications were compared between the mutant and the wild-type (WT) VLPs. The mutant VLP antigens were more specific, with higher positive predictive values and higher likelihood ratios than the WT VLP antigens. Both the SLEV and WNV mutant VLPs greatly reduced the observed cross-reactivity, significantly increasing the specificity and sensitivity of the assay. The use of these novel VLP antigens with reduced cross-reactivity in these serodiagnostic assays and others should lead to more accurate diagnoses of current infections, thereby reducing the need for time-consuming and cumbersome confirmatory plaque-reduction neutralization tests to differentiate between SLEV and WNV infections in North America.